Preparation and Photocatalytic Properties of Sr2-xAxFeMoO6 (X = 0, 0.1; A = Li, Na, K) - Zhai, Yong-Qing; Ma, Yu-Zhu; Qiu, Li-Ying; Jiang, Nan (Asian Journal of Chemistry, 2014)
In this paper, the sol-gel method is used to synthesize a series of double perovskite oxides Sr2FeMoO6 and Sr1.9A0.1FeMoO6 (A = Li, Na, K). The crystal structure was investigated by X-ray powder diffraction. The results show that all the as-synthesized samples have tetragonal crystal structure, small amount of substitution has little effect to the structure of Sr2FeMoO6 and they can keep double perovskite structure. Their photocatalytic activities were evaluated by degradation of dye acid black 10 B. The effects of the dosage of photocatalyst, irradiation time, irradiation source, initial concentration of dye solutions and alkali metal ions doping on the photocatalytic activity of samples were investigated. The results show that all the samples present high photocatalytic activities. In the dye concentration range of 20-150 mg/L, the decolorizing rate of acid black 10 B can reach above 95 % when the dosage of photocatalyst Sr2FeMoO6 is 100 mg under UV irradiation for 40 min. Moreover, the photocatalytic activity of Li-doped sample is lower than that of the un-doped sample, but the photocatalytic activity of the Na- or K-doped samples are much better than the un-doped sample and the decolorizing rate is nearly 100 %.